Manajemen Sarana Dan Prasarana Berbasis POAC (Planning, Organizing, Actuating, And Controlling) Dalam Mendukung Pengembangan Lembaga Pendidikan Islam Di MTI Canduang - Rafiqa Witri Asri; Zulfani Sesmiarni; Ali Mustopa Yakub Simbolon; Ulmadevi Ulmadevi (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
Thesis Title: “POAC-Based (Planning, Organizing, Actuating, and Controlling) Facilities and Infrastructure Management in Support of the Development of Islamic Educational Institutions at MTI Canduang” This thesis was written by Rafiqa Witri Asri, Student Identification Number 10222017, Islamic Education Management Study Program, Postgraduate Program, Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi. This study was motivated by the importance of facilities and infrastructure management in improving the quality of educational services and supporting the increased student admission capacity at Madrasah Tarbiyah Islamiyah (MTI) Canduang. The growing public interest in MTI Canduang requires effective facilities and infrastructure management, not only in providing adequate educational facilities but also in ensuring service sustainability through the systematic implementation of management functions. This study aims to analyze the implementation of the Planning, Organizing, Actuating, and Controlling (POAC) functions in facilities and infrastructure management and to identify the factors determining their effectiveness in supporting the institution's capacity development. This study employed a qualitative approach using a case study design to examine the implementation of the Planning, Organizing, Actuating, and Controlling (POAC) functions in facilities and infrastructure management at Madrasah Tarbiyah Islamiyah (MTI) Canduang. The research informants consisted of foundation leaders, boarding school leaders, facilities and infrastructure managers, teachers, and students selected through purposive sampling. Data were collected through in-depth interviews, observations, document analysis, and supporting surveys. Data trustworthiness was ensured through triangulation, while data analysis followed the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, conclusion drawing, and verification. The findings reveal that the effectiveness of facilities and infrastructure management is determined by the institution's ability to integrate actual needs, financial capacity, and stakeholder participation into the Planning process. Well-defined organizational arrangements, supported by effective coordination among managers, adaptive utilization of facilities, and continuous monitoring, contribute significantly to optimizing facilities and infrastructure management in supporting increased student admission capacity. Theoretically, this study strengthens the application of the POAC management framework within the context of facilities and infrastructure management in Islamic boarding school-based educational institutions by demonstrating that the effectiveness of each management function depends on the integration of management processes rather than on the isolated implementation of individual functions. The novelty of this study lies in the development of a POAC implementation model that links facilities and infrastructure management with student admission capacity as an indicator of institutional performance, thereby providing a new perspective for the development of sustainable and quality-oriented Islamic educational management.